2000
DOI: 10.1097/00001756-200002280-00038
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in the Wistar-Kyoto rat, a putative genetic animal model for depression

Abstract: The Wistar-Kyoto (WKY) rat exhibits several behavioral and hormonal abnormalities often associated with depression. One of the hallmarks of depression consists of alterations in the sleep-wake cycle, particularly in rapid eye movement (REM) sleep. If the WKY rat is indeed an animal model for depression, we hypothesized that it should also show sleep abnormalities relative to the control strain, the Wistar (WIS) rat Under baseline conditions, WKY rats showed a 50% increase in total REM sleep time during the 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 11 publications
5
57
0
Order By: Relevance
“…Globally, H mice had fragmented sleep, with notably a shorter duration of SWS bouts and a greater number of wake episodes, higher amounts of SWS 1 and REM sleep, and a shorter latency of this stage. These sleepwakefulness alterations in H mice are consistent with the data obtained in various depression models in the rat (Adrien et al, 1991;Dugovic et al, 2000;Nestler et al, 2002;Shiromani et al, 1988). Furthermore, they are reminiscent of sleep impairments observed in depressed patients, notably the sleep fragmentation, the shift towards lighter sleep stages, and the enhanced REM sleep pressure (Benca, 2000;Gillin et al, 1991).…”
Section: Locomotor Activity and Sleep-wakefulness Cycles Under Baselisupporting
confidence: 86%
See 3 more Smart Citations
“…Globally, H mice had fragmented sleep, with notably a shorter duration of SWS bouts and a greater number of wake episodes, higher amounts of SWS 1 and REM sleep, and a shorter latency of this stage. These sleepwakefulness alterations in H mice are consistent with the data obtained in various depression models in the rat (Adrien et al, 1991;Dugovic et al, 2000;Nestler et al, 2002;Shiromani et al, 1988). Furthermore, they are reminiscent of sleep impairments observed in depressed patients, notably the sleep fragmentation, the shift towards lighter sleep stages, and the enhanced REM sleep pressure (Benca, 2000;Gillin et al, 1991).…”
Section: Locomotor Activity and Sleep-wakefulness Cycles Under Baselisupporting
confidence: 86%
“…For both males and females, H mice exhibited significantly lower levels of wakefulness (ANOVA: F 1,220 ¼ 23.0, po0.001) and greater amounts of REM sleep (F 1,220 ¼ 21.2, po0.001) and SWS 1 (F 1,220 ¼ 78.0, po0.001) across the 24 h, compared to NH mice ( Figure 2, Table 2). SWS 2 was increased at the beginning of the dark period (Figure 2) but represented in the whole a smaller proportion of total sleep in H than in NH mice ( (Dugovic et al, 2000).…”
Section: Sleep and Wakefulnessmentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, others have tagged the WKY rats as a possibly stress-sensitive strain (Pare and Redei 1993;Pare and Kluczynski 1997). Numerous reports have indicated that the WKY rats display high anxiety and low locomotion reactivity compared with other strains (Pare 1992a(Pare , b, 1993(Pare , 1994Dugovic et al 2000). Likewise, the WKY have been proposed as an animal model of depressive behavior because they consistently demonstrate exaggerated behavioral and physiologic responses to stress in a variety of situations when compared with other strains (Pare 1993(Pare , 1994.…”
Section: Discussionmentioning
confidence: 99%